Do social cognitive factors influence final-year undergraduate students’ intentions to pursue advanced degrees? An examination of the moderating effect of sex - Bayon, Chembelyn; Abejo, Maximino; Guinocor, Marvin; Garciano, Martha Joyce; Literatus, Jonita; Reveche, Shaleen Jean; Nudalo, Arnel; Gonzaga, Maria Cristina; Caminos, Israeli; Caminos, Roger; Borres, Vincent; Cortes, Sylvester (Frontiers in Education, 2024)
This study explores the factors influencing final-year undergraduate students’ intentions to pursue advanced degrees through the lens of social cognitive theory (SCT). In addition, it investigates the moderating effect of sex on the causal pathways in the proposed model. Using a quantitative cross-sectional survey design, 578 final-year undergraduate students from various degree programs participated in an online survey. The results revealed that outcome expectations and social support are significant predictors of intention, while intention itself predicts the implementation of intentions to pursue an advanced degree. However, self-efficacy was not found to influence intention, and sex did not moderate the hypothesized paths in the model. These findings suggest that SCT provides a useful and robust framework for understanding the factors shaping undergraduate students’ intentions to pursue advanced degrees, as evidenced by the high explanatory power of the structural model. The study also offers practical and theoretical implications, along with suggestions for future research.